Mucus and Mucins: The Underappreciated Host Defence System - Sheng, Yong Hua; Hasnain, Sumaira Z. (Frontiers in Cellular and Infection Microbiology, 2022)
The mucosal surfaces that form the boundary between the external environment and the underlying tissue are protected by a mucus barrier. Mucin glycoproteins, both secreted and cell surface mucins, are the major components of the barrier. They can exclude pathogens and toxins while hosting the commensal bacteria. In this review, we highlight the dynamic function of the mucins and mucus during infection, how this mucosal barrier is regulated and how pathogens have evolved mechanisms to evade this defence system.